PENGARUH MINAT BELAJAR, PERILAKU BELAJAR, KECERDASAN SPIRITUAL DAN KECERDASAN ADVERSITAS TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Kasus Pada Mahasiswa S1 Universitas Kabupaten Bekasi, Kabupaten Karawang, Kabupaten Subang Dan Kota Bekasi) - Novia Paramita Afifah Susanto; Devi Astriani; Meliana Puspitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to evaluate and present empirical data on the effects of learning behavior, spiritual intelligence, adversity intelligence, and learning interest on accounting comprehension. The research employs a quantitative approach using primary data. The population consists of accounting students at universities in Bekasi Regency, Karawang Regency, Subang Regency, and Bekasi City who have completed six semesters. The sample determination uses purposive sampling, and the sample size is calculated using Slovin's formula. IBM SPSS version 26.0 is used for data analysis. The hypothesis is tested utilizing multiple linear regression analysis as a statistical technique. The findings show that the degree of accounting comprehension is positively impacted by learning interest, instructional behavior, mental ability, and adversity cognitive ability.